SEJARAH SOSlAL EKONOMI SUKU JAWA D1 KAMPUNG BARU KENAGARIAN SIKABAU KABUPATEN DHARMASRAYA TAHUN 1965-2012 - ZULMETRY, RILA - (Pendidikan Sejarah, 2014)
This paper discusses the Social and  Economic History of Javanese Kampung  Baru  Kenagarian  Sikabau Dharmasraya Year 1965-2012. The formulation of the problem in this study are as follows: What is the background arrival Javanese Kampung Baru Kenagarian Sikabau Dharmasraya 1965. Then how the development of social and economic life of the Javanese in Kampung Baru Kenagarian Sikabau Dharmasraya years 1965-2012. This thesis aims to look at how social and economic changes that occurred in the Java community in Kampung Ram Kenagarian Sikabau Dharmasraya. Writing method used is the historical method to phases: (I) Heuristics are searching for and collect information from primary and secondary sources. (2) Criticism Sources include internal and external criticism that the testing of the authenticity information. (3) Interpretation of interpreting and connecting the existing facts. (4) Historiography is the presentatio n of research results in the form of a thesis. The results showed that: 1) The Javanese Kampung Baru transmigration came from 1965 that has a background that is different as sharecroppers, agricultural laborers,construction workers and some have no work at all.2) The socio economic development of the Java community in Kampung Baru undergo changes. In the years 1999-2012 the Java community has experienced a movement of progress since they farmed rubber. With the rubber trees to make a change in the socio-economic life of the people of Java. From the social point visible from education, housing and lifestyle, wh ile visible in economic terms of income and livelihood, From the results of th is study concluded that: The Javanese in Kampung Baru from year 1965-2012 have ups and downs in his life. In addition, the interaction is atso.well established among the people of Java or Java community with the Minang community (the natives).